CONFLICT IN ORGANIZATIONS: ITS CONNECTION TO A HEALTHY AND PRODUCTIVE WORK ENVIRONMENT - Adinda Suci Cahya Ningtyas (Economic and Bussiness Faculty, Dr Soetomo University, 2024)
In this day and age, conflict is a topic that is still being discussed. Conflict cannot be completely avoided in an organization, but it can be managed by minimizing it. The study employed a qualitative approach using systematic literature review methods to analyze and synthesize existing research on organizational conflict and its implications for healthy and productive work environments. Data collection involved reviewing 30 articles from reputable national and international journals, focusing on conflict management, leadership styles, and the impact of external factors on organizational dynamics. Effective conflict management by organizational leaders is essential in fostering a cooperative environment for handling conflicts within teams. Constructive conflict management can lead to positive changes and learning experiences for all parties involved in organizational conflicts. Effective conflict resolution strategies can stimulate innovative problem-solving among employees and prevent a decline in motivation and creativity due to high levels of conflict.